Estudos biológicos de espécies de Puccinia utilizando Germinatélios - Aparecido, Christiane Ceriani; Passador, Martha Maria [UNESP] (My University, 2014)
Despite the importance of plant pathogens belonging to the Order Pucciniales (=Uredinales), popularly called rusts, certain peculiarities of its biology is poorly known, mainly due to the difficulty of growing them in culture media and also by the lack of appropriate methodologies for the development of research. Therefore, this study was to verify the efficiency of apparatus called germinatelia to obtain data about the basidiospores production biology of different Pucciniales species. Were used in the study Puccinia pampeana, P. psidii, P. pelargonii-zonalis, P. arachidis, P. mogiphanis, P. emiliae, P. hetereospora, P. malvacearum and P. cnici-oleracei. The use of germinatelia have revealed high basidiospores production for a period up to 5 months at temperatures between 12o and 21oC. Furthermore, in P. malvacearum was possible to record the germination by repetition (survival strategy) in 4.5% of basidiospores produced. All species were favored to mild temperatures. These results therefore demonstrate that the use of germinatélios is efficient, assisting in obtaining data about the biology and cycles of different Puccinia species, enabling better understanding of these pathogens, resulting in management and control measures most appropriate/accurate.
Biological studies of puccina species using Germinatelia
Keywords: Basidiospores production; Biological cycle; Methodology